Apparel and its Implications in Organizational Life: Clothing as a Regulatory Tool in Organizations - Maria Memória Viana , Lysia; Duarte, Márcia; Freitas Schilling Marquesan, Fábio (Organizações & Sociedade, 2025)
This essay aims to deepen the understanding regarding the role of attire and its implications in organizational life by proposing that organizational attire and its standardizing effect are essentially instruments of individual and collective disciplining and control, serving as integral components and conduits of power relations in organizational life. We argue that in a society where appearances play a fundamental role, what is worn on the body extends beyond functional and aesthetic layers and serves as a significant mirror of the functioning of social mechanisms, indicating deeper connections related, for example, to culture, social function, belongingness, and desires. The theoretical framework underpinning the discussion is primarily based on Foucault’s work (2006), wherein the contribution lies in the proposal of a theoretical perspective composed of four phases of attire’s influence on individuals, ranging from the moment the body is dressed to its effects when they become generalized and collectively internalized.